Pendampingan Bacaan Al-Fatihah Dengan Baik Dan Benar Sesuai Ilmu Tajwid di Desa Kebonrejo Kediri - Ika Setyowati; Silvia Shofiyatun Naja (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
This research is a research carried out in order to carry out the tridharma of higher education at the Faqih Asy’ari Islamic Institute (IAIFA) Kediri. This type of research is Community Service Research (PKM). This research will be carried out objectively and researchers will participate in providing assistance. The purpose of this study is to provide assistance in understanding al fatihah readings related to recitation. So that the children of the An-Nur prayer room can read al fatihah with tartil and fashih. The method that will be used in this study uses descriptive research which is a research procedure or problem solving investigated with a description of the subject or object used by people, institutions, communities and others. Therefore, this approach is a means to remind children’s awareness properly and correctly in reading al fatihah according to tajwid. With the descriptive method, the research allows to conduct relationships between variables, test hypotheses related to current circumstances and events